2004
DOI: 10.3136/fstr.10.75
|View full text |Cite
|
Sign up to set email alerts
|

Banana Polyphenol Oxidase: Occurrence and Change of Polyphenol Oxidase Activity in Some Banana Cultivars during Fruit Development

Abstract: Occurrence of polyphenol oxidase (PPO, o-diphenol: oxygen oxidoreductase, EC.1.10.3.1) in the fruits of nine cultivars of banana (Musa spp.) commercially cultivated in China was investigated. All banana fruits peel and pulp tested had PPO activity, and all PPO strongly oxidized dopamine and 3-hydroxytyramine (tyramine). However, very weak and/or no oxidative activity was recognized on such trihydroxybenzenes as phloroglucinol and gallic acid. Similar substrate specificity of PPOs toward phenolic compounds was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…5), they had a significant difference between 70 DPA and 90 DPA. Similar results were reported that PPO activities of banana and litchi fruits were high at the initial stage, then declined gradually, and finally tended to increase by the end of fruit development (Yang et al, 2004;Sun et al, 2009). The curve for POD activity showed four peaks throughout the development of longan fruit.…”
Section: Changes Of Ppo and Pod Activitiessupporting
confidence: 88%
“…5), they had a significant difference between 70 DPA and 90 DPA. Similar results were reported that PPO activities of banana and litchi fruits were high at the initial stage, then declined gradually, and finally tended to increase by the end of fruit development (Yang et al, 2004;Sun et al, 2009). The curve for POD activity showed four peaks throughout the development of longan fruit.…”
Section: Changes Of Ppo and Pod Activitiessupporting
confidence: 88%
“…However, to date, there are no studies on the effect of GB application on climacteric tropical fruits. It has been reported that the browning (lowtemperature injury symptom) in banana peel is caused by the oxidation of polyphenols caused primarily by polyphenol oxidase (PPO) (Yang et al [20]). Nguyen et al [21] report that banana fruits exposed to low temperatures experience an increased activity of both phenylalanine ammonia lyase (PAL) and PPO.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme PPO (EC 1.10.31) is found in the tissue of a wide range of fruits and vegetables, and is responsible for the browning discoloration observed in many plant food materials (Dry and Robinson 1994;Broothaerts et al 2000;Chen et al 2000;Okot-Kotber et al 2002;Leja et al 2003;Yang et al 2004;Casado-Vela et al 2005). PPO catalyzes mono-and o-diphenol conversion to o-quinones during ripening and during postharvest handling, storage and processing (Richard-Forget et al 1998;Nkya et al 2003;Casado-Vela et al 2005;Selles-Marchart et al 2006;Spagna et al 2005).…”
Section: Introductionmentioning
confidence: 99%